Atemoia, muito além do sabor doce e aroma agradável: presença de compostos bioativos e capacidade biossorvente - Venceslau, Adneia de Fátima Abreu (2021)
Atemoya is a hybrid from an artificial interbreeding made in Florida (USA) in1908 between ata (Annona squamosa L.) and cherimoya (Annona cherimola Mill.). Based on a concept of circular economy, in which the raw material of a production chain is the waste from another, the full-spectrum utilization of the atemoya var Thompson fruit has been proposed. The peel has originated two effective biosorbents for methylene blue, one submitted to alkaline treatment and one in natura, with pHPZC values close to neutral, and at least 80% removal. The kinetic profile has been adjusted by pseudo-second order method, and best adjustment for D-R isotherm for both biosorbents, with maximum biosorption capacity of 190.18 mg g-1 (in natura) and 264.50 mg g-1 (with alkaline treatment) at 45 °C, being reusable for at least 5 cycles. From the seeds, the oil has been extracted through three different ways (mechanically, chemically, and by partitioning) and the most abundant constituents have been identified. Mechanical extraction: elaidic acid (66,11%) and stearic acid (6,67%); chemical extraction: (Z)-hexadec-9-enal (49,42%) e triolein (23,28%). By partitioning the following fractions have been obtained, OSAHM: dihydroxyacetone (19,16%) and 3-deoxy-d-mannoic lactone (16,34%); OSAHEX: gamma-sitosterol (31,73%) e erucic acid (14,64%); OSACLO: gamma-sitosterol (22,11%) and vaccenic acid (15,49%); OSAACE: (Z)-icos-9-enoic acid (31,28%) and beta-sitosterol (16,29%). Among the constituents identified, 12 have already been identified as potential adjuvant therapy for SARS-COV 2, and others have already been confirmed to have a variety of biological activities.